2021
DOI: 10.2196/31264
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Needs During Natural Disasters: Mixed Methods Analysis of Portal Messages Sent During Hurricane Harvey

Abstract: Background Patient portals play an important role in connecting patients with their medical care team, which improves patient engagement in treatment plans, decreases unnecessary visits, and reduces costs. During natural disasters, patients’ needs increase, whereas available resources, specifically access to care, become limited. Objective This study aims to examine patients’ health needs during a natural crisis by analyzing the electronic messages sent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The studies that assessed the role of pharmacies post-EWCEs (N = 13) showed the importance of pharmacists in providing care to individuals impacted by EWCEs ( Table 2 ). 5 - 17 However, these studies also revealed that many pharmacies were not equipped with disaster preparedness protocols despite the existence of statewide policies to help pharmacies lead disaster recovery efforts. 8 This lack of disaster preparedness affected the functionality and accessibility of pharmacies in times when care was most needed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies that assessed the role of pharmacies post-EWCEs (N = 13) showed the importance of pharmacists in providing care to individuals impacted by EWCEs ( Table 2 ). 5 - 17 However, these studies also revealed that many pharmacies were not equipped with disaster preparedness protocols despite the existence of statewide policies to help pharmacies lead disaster recovery efforts. 8 This lack of disaster preparedness affected the functionality and accessibility of pharmacies in times when care was most needed.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that issues with accessing pharmacies and medications post-EWCEs are often due to pharmacy closures, inability to contact prescribers, and insurance challenges. 5 - 7 , 9 , 12 , 13 In 1 paper, barriers that prevented patients from accessing medications included restrictive insurance benefits, patients’ resistance to mail order, and higher copayments for larger prescription units. 6 A study interviewed patients of community pharmacies in Puerto Rico after Hurricane Maria to assess patients’ medication needs and level of satisfaction with community pharmacy services.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations